Outcome of Surgery in Ruptured Aneurysm: A Study of 48 Cases (Bangladesh Journal of Neurosurgery, 2024)
Background : Rupture aneurysm is a dangerous clinical condition of a patient. The  aim of this study is to find out the outcome of rupture aneurysm after microsurgical  clipping.Method: This was a prospective cross sectional study and was conducted at the  department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University, Dhaka  from January 2011 to April 2022.Results : Among 48 patient 30(62.5%) were male. It was documented that 32(66.6%)  patients were belong to 51-60 years. It was evident that the most of the clinical  presentation was history of sudden severe headache 48(100%), 32(66.6%) patients  had presented with vomiting and brief loss of consciousness had 24(50%). The  highest percentage of WFNS grading of during admission were (1-3), 32(66.6%). Peroperative  rupture during surgery were 16(33.33%). During discharge good recovery  was occurred 38(79.7%) and 5(10.5%) had death.Conclusion: We have treated all the case by microsurgical clipping. Still microsurgical  clipping is one of the gold standard procedure for rupture intracerebral aneurysm. Bang. J Neurosurgery 2023; 12(2): 114-121